Seasonality in phytoplankton communities and production in three Arctic fjords across a climate gradient - Cheshtaa Chitkara; Thomas Juul-Pedersen; Diana Krawczyk; Janne E. Søreide; Anna Vader; Rolf Gradinger; Mie HS Winding; Tobias R Vonnahme (Progress in Oceanography, 2024)

Seasonal Variability in the Zooplankton Community Structure in a Sub-Arctic Fjord as Revealed by Morphological and Molecular Approaches - Estelle Coguiec; Elizaveta A. Ershova; Malin Daase; Tobias R. Vonnahme; Owen S. Wangensteen; Rolf Gradinger; Kim Præbel; Jørgen Berge (Frontiers in Marine Science, 2021)
Phyto- and zooplankton in Arctic and sub-Arctic seas show very strong seasonal changes in diversity and biomass. Here we document the seasonal variability in the mesozooplankton community structure in a sub-Arctic fjord in Northern Norway based on monthly sampling between November 2018 and February 2020. We combined traditional morphological zooplankton identification with DNA metabarcoding of a 313 base pair fragment of the COI gene. This approach allowed us to provide the most detailed mesozooplankton species list known for this region across an entire year, including both holo- and meroplankton. The zooplankton community was dominated by small copepods throughout the sampling period both in terms of abundance and relative sequence counts. However, meroplankton was the most diverse group, especially within the phylum polychaeta. We identified four distinct periods based on the seasonal analysis of the zooplankton community composition. The pre-spring bloom period (February–March) was characterized by low abundance and biomass of zooplankton. The spring bloom (April) was characterized by the presence of Calanus young stages, cirripedia and krill eggs. The spring-summer period (May–August) was characterized by a succession of meroplankton and a relatively high abundance of copepods of the genus Calanus spp. Finally, the autumn-winter period (September–December) was characterized by a high copepod diversity and a peak in abundance of small copepods (e.g., Oithona similis , Acartia longiremis , Pseudocalanus acuspes , Pseudocalanus elongatus , Pseudocalanus moultoni , Pseudocalanus minutus ). During this period, we also observed an influx of boreal warm-water species which were notably absent during the rest of the year. Both the traditional community analysis and metabarcoding were highly complementary and with a few exceptions showed similar trends in the seasonal changes of the zooplankton community structure.

Crude oil exposure reduces ice algal growth in a sea-ice mesocosm experiment - Kyle Dilliplaine; Marc Oggier; R. Eric Collins; Hajo Eicken; Rolf Gradinger; Bodil A. Bluhm (Polar Biology, 2021)

What Feeds the Benthos in the Arctic Basins? Assembling a Carbon Budget for the Deep Arctic Ocean - Ingrid Wiedmann; Elizaveta Ershova; Bodil Annikki Bluhm; Eva-Maria Nöthig; Rolf R. Gradinger; Ksenia Kosobokova; Antje Boetius (Frontiers in Marine Science, 2020)

Fatty acid and stable isotope characteristics of sea ice and pelagic particulate organic matter in the Bering Sea: tools for estimating sea ice algal contribution to Arctic food web production - Shiway W. Wang; Suzanne M. Budge; Rolf R. Gradinger; Katrin Iken; Matthew J. Wooller (Oecologia, 2014)

Editorial - Arctic Ocean Diversity: synthesis - Bodil A. Bluhm; Rolf Gradinger; Russell R. Hopcroft (Marine Biodiversity, 2011)

Using stable isotopes to assess carbon and nitrogen turnover in the Arctic sympagic amphipod Onisimus litoralis - Mette R. Kaufman; Rolf R. Gradinger; Bodil A. Bluhm; Diane M. O’Brien (Oecologia, 2008)

Abundance and composition of the sea-ice meiofauna in off-shore pack ice of the Beaufort Gyre in summer 2002 and 2003 - Rolf R. Gradinger; Klaus Meiners; Gerry Plumley; Qing Zhang; Bodil A. Bluhm (Polar Biology, 2005)